Albuminuria Is Associated with Steatosis Burden in Patients with Type 2 Diabetes Mellitus and Nonalcoholic Fatty Liver Disease (Diabetes Metab J 2021;45:698-707) - Han, Eugene; Kim, Hye Soon (Diabetes & metabolism journal, 2021)
[...]it is possible that patients with earlier stages of NAFLD compared with that of a previous Chinese study [7] may have been enrolled, and thus, distinct results were obtained. NOTES CONFLICTS OF INTEREST No potential conflict of interest relevant to this article was reported. 1. EASL clinical practice guidelines on non-invasive tests for evaluation of liver disease severity and prognosis: 2021 update.